2003
DOI: 10.1016/s0042-6989(03)00408-5
|View full text |Cite
|
Sign up to set email alerts
|

Contrast coding and magno/parvo segregation revealed in reaction time studies

Abstract: Reaction times (RTs) are obtained for a wide range of contrasts of vertical sinusoidal gratings. The data are plotted as a function of the reciprocal of contrast. In some conditions, a single linear function accounts for the data. In others a clear bi-linear function is obtained. The low and high contrast regions of the function are interpreted as representing magno and parvo activity, respectively. RT-based supra-threshold sensitivity functions are obtained for different luminances, stimulus durations and ecc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
72
0
22

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(101 citation statements)
references
References 71 publications
7
72
0
22
Order By: Relevance
“…Pooled across the relevant experiments, 10 the correlation (r) between T1 performance and T1-distractor relative contrast was .84 ( p Ͻ .001). These results either replicate or are consistent with those in the psychophysical literature (Ejima & Otani, 1987;Gish et al, 1986;Lupp et al, 1976;Murray & Plainis, 2003;Plainis & Murray, 2000;Tiipana, Paramei, & Alshuth, 2001). …”
Section: Target Contrast and Performancesupporting
confidence: 89%
See 1 more Smart Citation
“…Pooled across the relevant experiments, 10 the correlation (r) between T1 performance and T1-distractor relative contrast was .84 ( p Ͻ .001). These results either replicate or are consistent with those in the psychophysical literature (Ejima & Otani, 1987;Gish et al, 1986;Lupp et al, 1976;Murray & Plainis, 2003;Plainis & Murray, 2000;Tiipana, Paramei, & Alshuth, 2001). …”
Section: Target Contrast and Performancesupporting
confidence: 89%
“…Detection and identification performance is a monotonically increasing function of contrast (Graham, 1989). Reaction time to a spatial pattern decreases as its contrast increases (Ejima & Ohtani, 1987;Gish, Shulman, Sheehy, & Leibowitz, 1986;Lupp, Hauske, & Wolf, 1976;Murray & Plainis, 2003;Plainis & Murray, 2000;Thompson & Drasdo, 1989), implying that increases in contrast allow faster information accumulation and/or improve processing efficiency. The neurophysiological evidence accords well with the psychophysical data.…”
Section: Varying Target and Distractor Contrastmentioning
confidence: 99%
“…The decrease of reaction times with increasing stimulus contrast is much steeper for contrasts below 10% than it is for larger contrasts (e.g. Murray and Plainis 2003). Therefore, we expect larger beneWts of attention in our experiment, because we used a contrast of 7.1% for our low-contrast target.…”
Section: Materials and Stimulimentioning
confidence: 85%
“…In the honeybee, several experiments (reviewed by Lehrer 1993b) revealed that colour, shape and motion are processed in parallel and independently, a conclusion already drawn for human vision from psychophysical tests (Livingstone and Hubel 1987;Shiller and Logothetis1990;Burr et al 1994;Murray and Plainis 2003) (but see Gegenfurtner and Hawken 1996;Willis and Anderson 2002).…”
Section: Generalization Among Different Types Of Contrastmentioning
confidence: 86%